SPATIAL ANALYSIS OF RESIDENTIAL DEVELOPMENT IN PALU CITY - Westi Utami; Abdul Muzil; Deny Andriawan; Maryono Dwi Saputra; Weni Yolanda Ratnasari (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2020)
The earthquake, tsunami, and liquefaction that hit Palu in 2018 damaged infrastructure and settlements and resulted in 2,101 fatalities. In this context, understanding the level of vulnerability and disaster mitigation is very important, especially in providing directions for spatial use. This study aimed to map the affected areas, map the suitability of land use against spatial planning, and map settlement development in Palu City. Data analysis was carried out spatially through an overlay of spatial pattern maps with disaster-affected areas to map the disaster-affected areas. Next, an overlay was carried out on the land use with the Regional Spatial Plan (RTRW) to map the suitability of land use. Finally, an overlay of disaster-prone space zones was carried out on spatial patterns to map the classification of settlement zones. The results of the analysis show that in Palu City there are locations that are suitable for settlement and development covering an area of 5233.978 Ha or 13%; an area that can be used but conditional for settlement is 26860.36 Ha or 68%; the area that can be used but with certain conditions is 3106,714 Ha or 8%; while the land area of 4057,112 ha or 10% is a forbidden zone. This study is expected to become a consideration for the community in building settlements as well as a consideration in preparing spatial plans to suit disaster mitigation efforts. This effort is made so that the construction of post-disaster settlements is carried out in disaster-safe areas.